The Role of Progressive Muscle Relaxation and Cognitive Behavioral Therapy to Control Insomnia Among Elderly - Apriany, Anita; Aljaberi, Musheer Abdulwahid (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Introduction: Insomnia is a prevalent medical condition that impacts people across a lifetime. Diagnosis is established through self-reported symptoms including daytime disruptions and poor sleep quality, notwithstanding the provision of sufficient sleep opportunities and a conducive sleeping environment. Untreated insomnia is correlated with a variety of detrimental health consequences. The aim of the study was to analyze the role of progressive muscle relaxation (PMR) and cognitive behavioral therapy (CBT) to control insomnia. Material and Menthods: The research used is qualitative research, a review of the relevant literature constitutes this research. Themes-aligned articles from the years 2019 to 2024 were chosen, to comply with the prescribed research protocol, the investigators utilized the PRISMA method. Results: Nine articles were chosen from fifteen publications based on the search technique and selection criteria, and finding that PMR and CBT approach was helpful in assisting in the improvement of insomnia in elderly. Conclusion: Based on the conducted literature review, non-pharmacological treatments for addressing insomnia in older adults include progressive muscle relaxation (PMR) and cognitive behavioral therapy (CBT) interventions. Both of these approaches have demonstrated significant efficacy in managing insomnia in this population.